KEBIJAKAN PENDIDIKAN DALAM MENINGKATKAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN FIQIH - Rahma, Cut Dewi; Silahuddin, Silahuddin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
Education policy refers to decisions or regulations made by the government or educational institutions to organize, manage, and improve the education system in order to achieve the desired educational goals. The policy on enhancing students' critical thinking skills in Fiqh education at SMA Dayah Perbatasan Minhajussalam, Subulussalam City, still faces some challenges, thus requiring further investigation. This study aims to examine the education policy in improving students' critical thinking skills in Fiqh lessons at SMA Dayah Perbatasan Minhajussalam. The research methods used are qualitative descriptive by collecting data through interviews, observations and using the data analysis of the Miles and Huberman model including data reduction, data presentation, conclusion drawn/verification. The research method used is descriptive qualitative, with data collection through interviews, observations, and document analysis. The results show that the education policy at SMA Dayah Perbatasan Minhajussalam has successfully integrated a critical thinking approach into the Fiqh curriculum. Additionally, the teaching of Fiqh at this school also supports the development of students' critical and reflective attitudes toward religious understanding and social context. This study recommends the need for increased teacher training to optimize teaching techniques that promote students' critical thinking skills within the context of Fiqh education.